2016
DOI: 10.3390/jof2020017
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Bronchopulmonary Aspergillosis

Abstract: Allergic bronchopulmonary aspergillosis (ABPA), a progressive fungal allergic lung disease, is a common complication of asthma or cystic fibrosis. Although ABPA has been recognized since the 1950s, recent research has underscored the importance of Th2 immune deviation and granulocyte activation in its pathogenesis. There is also strong evidence of widespread under-diagnosis due to the complexity and lack of standardization of diagnostic criteria. Treatment has long focused on downregulation of the inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 119 publications
(161 reference statements)
0
93
0
2
Order By: Relevance
“…Allergic disease associated with fungal antigens, including the best characterized such syndrome, ABPA, is beyond the scope of this review. ABPA in CF, present in up to 20% of CF patients, carries significant morbidity, and is considered in detail elsewhere . National cystic fibrosis registry data in the USA is limited by a lack of standardization in protocols for collecting and analyzing samples.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Allergic disease associated with fungal antigens, including the best characterized such syndrome, ABPA, is beyond the scope of this review. ABPA in CF, present in up to 20% of CF patients, carries significant morbidity, and is considered in detail elsewhere . National cystic fibrosis registry data in the USA is limited by a lack of standardization in protocols for collecting and analyzing samples.…”
Section: Epidemiologymentioning
confidence: 99%
“…ABPA in CF, present in up to 20% of CF patients, carries significant morbidity, and is considered in detail elsewhere. [1][2][3] National cystic fibrosis registry data in the USA is limited by a lack of standardization in protocols for collecting and analyzing samples. The most commonly described fungi in registry data are yeasts, specifically Candida spp., and the filamentous fungus Aspergillus.…”
Section: Epidemiologymentioning
confidence: 99%
“…These abnormalities allow persistence of A. fumigatus in the airways allowing them to germinate into hyphae. 3 In susceptible individuals, colonisation is followed by Aspergillus sensitisation, which is defined as immune-mediated response to A. fumigatus, without evidence of inflammation or tissue damage. 4 Aspergillus sensitisation is currently believed to be the first step in the pathogenesis of ABPA.…”
Section: Introductionmentioning
confidence: 99%
“…The role of omalizumab in ABPA management is being increasingly appreciated. 9 A review of 102 published cases of ABPA treated with omalizumab concluded that the drug helped mitigate symptoms, improve PFTs, and decrease corticosteroid requirements. 10 With the increasing use of omalizumab in refractory ABPA, there is interest in developing monoclonal antibodies that target other portions of ABPA's inflammatory cascade.…”
Section: Discussionmentioning
confidence: 99%